Development and in vitro Evaluation of Atazanavir Microcrystals for Intranasal Delivery - Paul, Swarnali Das; Deshmukh, Rohitas; Kukreja, Simran (Indian Journal of Pharmaceutical Education and Research, 2022)
Background: Nasal route of drug administration has gained popularity nowadays specially for drugs acting on nasopulmonary area. Atazanavir is an antiviral drug which has proved efficacy in different viral infection including COVID-19. Therefore the hypothesis is, if given through intra nasal route this formulation will be able to prevent the viral infection like COVID-19 by directly acting on the virus at its entry point. Objectives: This study aims to prepare a stable mucoadhesive microcrystal formulation of this antiviral drug with good permeation for intra nasal delivery. Materials and Methods: The formulation was prepared by high-speed homogenization process. Prepared microcrystals were estimated for in vitro drug release and permeation, drug excipient interaction study by DSC, FTIR and in vitro mucoadhesiveness study on agar gel plate. A short-term stability study was conducted on all formulations for 6 months. Results: The melting point and absorbance maxima of atazanavir were found as 200.9°C and 248 nm. The DSC and FTIR study results confirmed no drug excipient interaction was there in the formulation. The particle size of the formulations was found as 5-11 μm in range. Drug release was better and faster from the microcrystals as compare to pure powder drug. The flux for microcrystal formulation was found to be 100 whereas flux for the pure drug powder was 24. Formulations had sufficient mucoadhesive strength due to incorporation of HPMC 400 polymer and they were found stable after six months stability study. Conclusion: Lastly, it can be concluded that this formulation would be a promising system for the delivery through intra nasal route as it showed good drug release and permeation during a short time span in in vitro nasal condition with a particle size range suitable for intranasal delivery. However, further in vivo studies are required to confirm the hypothesis.
Keywords: COVID-19; Atazanavir; Protease inhibitor; Naso-pulmonary; Intranasal; Antiviral